Migration Characteristics and Restoration Mechanism of Grout Containing Aggregate in Overburden Fractures Based on CFD-DEM Coupling Model - Yulou Ren; Feng Du; Huanqi Chen; Zijie Hong; Ziyuan Ren (Geofluids)
In order to improve and restore the strength and stability of broken overburden caused by coal seam mining in underground, the grout containing aggregate is employed to backfill specific fracture space in rock strata, which is an important method to prevent the mine water leakage and roof collapse in working face. Therefore, the migration characteristics and restoration mechanism of grout containing aggregate in overburden fractures based on the CFD-DEM coupling model are researched in this paper. Specifically, the mechanical constitutive model of aggregate migration is obtained by mechanical analysis of particles and flow field, and the mechanism of aggregate flow and transport with grout in rock fracture is put forward. Besides, the coupled CFD-DEM model is built by numerical simulation software, and the transport process of grout containing aggregate in the fracture is numerically calculated. On this basis, the transport law and deposition characteristics of aggregate transport with grout are studied, and the inner mechanism of the change law is obtained. The research results indicate that the aggregate is gradually deposited by various “settlement forces” during the migration process. The smaller the particle size and density of aggregate are, the slower the deposition rate of aggregate particles and the longer the migration distance are. The aggregate with particle size of 3 mm and density of 3250 migrates 1.25 m to reach the maximum solid ratio of 12.9%. The settlement ratio reaches 100% after migration of 1.5 m, and the longest migration distance is 1450 mm. In addition, the solid ratio of each aggregate firstly increases and then decreases with its migration, which is analyzed from the perspective of aggregate deposition and concentration change. When the aggregate density of two particle sizes changes from 3500 to 3750, the aggregate migration distance is significantly reduced. The research results provide an important guiding significance for reasonably selecting aggregate parameters and optimizing the design of grouting holes in mining engineering.